HEALTH CHALLENGES OF URBANIZATION - Onwunaka, Chinagorom; Nwimo, Dr.Ignatius (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Urbanization is rapid population growth in urban areas and is often due to internal migration from rural to urban areas. In many countries urban areas are characterized by size and population density and in some developing countries the availability of electricity and piped water is also taken into consideration. Urban areas face many health challenges including mental health, intimate-partner violence and alcohol abuse, HIVIAIDS, malaria, tuberculosis (TB), indoor airpollution, outdoor airpollution, trafficrelated injuries and deaths and risks from climate change. Thefocus of World Health Day 2010 was on the health challenges presented by an increasingly urbanized world. WorldHealth Day 2010 provided a unique opportunity topromote and develop visionary plans and programmes to address health issues in cities all over the globe. Health issues in urban areas often merit attention regardless of the socioeconomic status of the countries involved. It is projected that by 2030, more people in the developing world will live ,in urban than rural areas and by 2050, two-thirds of its population is likely to be urban. The world’s population asa whole is expected to grow by 2.5 billion from 2007 to 2050, with the cities and towns of developing countries absorbing almost all of these additional people. This demographic transformation might aggravate the health problems already experienced in urban cities across the globe. Therefore there is need toplan interventions that might reduce the negative health implications of urbanization on urban dwellers This paper therefore discusses the health challenges of urbanization.